Annuities in Switzerland - Bütler, Monika; Ruesch, Martin (World Bank, Washington, DC, 2012)
Switzerland's pension system has attracted considerable attention, mainly due to its reliance on a three-pillar structure. A relatively small pay-as-you-go system (first pillar) is complemented by a mandatory, employer-based, fully funded occupational pension scheme (second pillar). The main goal of this paper is to provide a detailed description and analysis of the Swiss pension system. Particular emphasis is placed on the second pillar and its role in the provision of old age benefits within the Swiss social security system. The paper shows, for example, that a typical individual with an uninterrupted career can expect a net (after-tax) replacement rate of at least 70 percent. Occupational pension plans are highly regulated. Minimum interest rate requirements and minimum conversion rates (at which the accumulated retirement balances are transformed into annuity streams) introduce many elements of defined benefit plans into notionally defined contribution schemes. The resulting money's worth ratios are very high (with the exception of single males). Switzerland also has a high annuitization rate by international standards (approximately 80 percent). However, due to high fragmentation of the scheme and non-uniform accounting practices, some aspects of the system are not very transparent. The paper sheds light on the financial health of the pension system and the evolution of the regulatory framework in the past two decades.